Clinical characteristics and molecular detection of in hospitalized children with a clinical diagnosis of whooping cough in Peru. - Del Valle-Mendoza, Juana (2021)
Pertussis is an infectious disease caused by the Gram-negative bacterium Bordetella pertussis. In Peru, actual public health programs indicate that vaccination against B. pertussis must be mandatory and generalized, besides all detected cases must be reported. The objective of this study was to determine the prevalence of B. pertussis among children under five years of age with a presumptive diagnosis of whopping cough in Cajamarca, a region located in northern Peru.